(untitled) (Eurasian Scientific Herald, 2022)
The effect of aerobic capacity and cardiovascular status on players after training has been studied. Aerobic performance indicators of the body of the studied players were moderate. There are also individual differences between the level of functional indicators in most players and the response of the cardiovascular system to the load